The contribution of food consumption value in shaping food destination image and behavioral intention: The perspective of foreign tourists in Bali - Valerie, Celine; Marcia, Kimiyana; Kristanti, Monika; Thio, Sienny (Universitas Tarumanagara, 2024)
Eating local dishes at a tourist’s destination is crucial. This study explores the key drivers of foreign tourists’ behavioral intention toward local Indonesian food. A model examining food consumption value, food destination image, and behavioral intention was investigated using partial least squares structural equation modeling (PLS-SEM). This descriptive study involved quantitative data using a five-point Likert scale questionnaire as the data collection method. The sampling method was judgmental, where the respondents were 201 foreign tourists visiting Bali and sampled local cuisine. The author distributed questionnaires to foreign tourists through online and onsite visits to tourism places and restaurants in Bali. The findings reveal that the impact of food consumption value on behavioral intentions is partially mediated by food destination image. This means that while food consumption value positively and significantly affects behavioral intentions, it also significantly influences behavioral intention through tourists’ perceptions of the destination. Food consumption value has a significant influence on food destination image and food destination image has a significant influence on the behavioral intention of foreign tourists. The findings imply that food business owners and food destination marketers need to strategically develop and design effective promotions to promote local food and build a good image of a food destination to attract more foreign tourists.